Managing talent recruiting, retaining and getting the most from talented people - Devine, Marion; Syrett, Michel (PublicAffairs, 2014)
Using research and interviews with industry experts at "talented" companies including Ford, Goldman Sachs and Cisco, describes how to find the most talented workers and keep them happy, challenged and engaged so that they stay and don't seek employment elsewhere
"The Economist in association with Profile Books Ltd. and PublicAffairs"...T.p. verso. - "First published in 2014 by Profile Books Ltd. in Great Britain"...T.p. verso. - Includes bibliographical references and index
Keywords: Manpower planning; Human capital; Employees -- Recruiting; Employee retention; Career development